Presencia de diastemas patológicos y su relación con frenillo labial superior hipertrófico en niños de 6 a 13 años de edad pertenecientes a la Unidad Educativa Giovanni Antonio Farina San Gabriel - Valle de los Chillos - Cruz Proaño, Andrea Paola (2017)
In childhood, it is common to observe the presence of Diastema interincisal, especially in ages from 6 to 9 years, which will decrease as age increases and definitive pieces erupt, such as the canines and the second definitive molar. The half interincisal Diastema, is the space that is located in the maxilla or mandible between central incisors, which is classified as normal or, in turn, pathological. A normal diastema is defined as the one found in the midline and is caused by the age of dental eruption in which the infant is found (Ugly Duckling Age). A pathological Diastema is caused by etiological factors, this study will analyze the presence of this diastema related to Hypertrophic Frenillo, being this the most frequent etiological factor in the population. Hypertrophic Frenillo: is a band of muscle tissue of very fibrous consistency, is inserted at the level of the interincisiva or palatine papilla, its insertion is very low. Its main function is to join the lip with the gingiva, but this being to be hypertrophic, will be the main cause of a Diastema interincisal and other problems of type: phonetic, periodontal, orthodontic and an esthetic. The present study was carried out in the Educational Unit Geovanni Antonio Farina. Each participant was assessed by a clinical examination the presence of a pathological diastema related to hypertrophic frenulum, in addition we performed the Graber maneuver to check this etiology. We had as a result, in the study after evaluating each of the following variables; the prevalence of non-pathological diastema was 86 percent of the sample. Pathological diastema related to hypertrophic frenulum 33 percent. The consistency of the upper lip frenulum was higher in the normal percentage with 1 percent